О ганкелевых определителях функций, заданных своим разложением в P-дробь - Буслаев, В.И. (Український математичний журнал, 2010)
Одержано явні формули, що виражають ганкелеві визначники функцій, які задано своїм розвиненням у неперервний P-дріб, через параметри дробу. Як наслідок отримано оцінку знизу ємності множини особливих точок таких функцій, аналог теореми Ван Флека для P-дробів з граничними періодичними коефіцієнтами, інше доведення теореми Гончара про гіпотезу Лейтона, оцінку зверху радіуса кола мероморфності функції, що задана С-дробом. We obtain explicit formulas that express the Hankel determinants of functions given by their expansions in continued P-fractions in terms of the parameters of the fraction. As a corollary, we obtain a lower bound for the capacity of the set of singular points of these functions, an analog of the van Vleck theorem for P-fractions with limit-periodic coefficients, another proof of the Gonchar theorem on the Leighton conjecture, and an upper bound for the radius of the disk of meromorphy of a function given by a C-fraction.